2017
DOI: 10.1108/jadee-02-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perceptual differences on consumer purchase intention of natural functional food

Abstract: Purpose The concept of functional foods is not new to the Malaysian people. Functional foods as traditional medicine have made tremendous contributions over the past couple of centuries. The growth in the economy, coupled with a strong desire among the Malaysian consumers to maintain a healthy lifestyle has made functional foods an alternative medicine among the populace. Although the consumption of functional foods is increasing in Malaysia, relatively little is known about the factors which affect consumer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 41 publications
7
54
0
Order By: Relevance
“…Subjective norms represent group influence or social pressure to perform the behavior [27][28][29]. The TRA has proved to be an effective model that can explain and predict consumer attitude, intention, and behavior relating to food products including functional foods [30][31][32][33].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Subjective norms represent group influence or social pressure to perform the behavior [27][28][29]. The TRA has proved to be an effective model that can explain and predict consumer attitude, intention, and behavior relating to food products including functional foods [30][31][32][33].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Subjective norms represent group influence or social pressure to perform the behavior [27][28][29]. The TRA has proved to be an effective model that can explain and predict consumer attitude, intention, and behavior relating to food products including functional foods [30][31][32][33]. Given that subject norm was found to be a weak determinant of intention, several authors have suggested to examine the linkage between subjective norm and attitude [19,34,35].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations